A New Flow Cytometry-Based Single Platform for Universal and Differential Serodiagnosis of HTLV-1/2 Infection - Pimenta de Paiva, Luciene; Coelho-dos-Reis, Jordana Grazziela Alves; Trindade, Bruno Caetano; Peruhype-Magalhães, Vanessa; Silva Araújo, Márcio Sobreira; Gonçalves, Juan Jonathan; Nogueira-Souza, Ana Caroline; Pereira Martins, Júlia; Lopes Ribeiro, Ágata; Starling, Ana Lucia; Alcântara, Luiz Carlos Júnior; Ribeiro, Maísa Aparecida; et al. (Frontiers in Immunology, 2022)
In the present work, we developed and evaluated the performance of a new flow cytometry-based single platform, referred to as “FC-Duplex IgG1 (HTLV-1/2)”, for universal and differential serodiagnosis of HTLV-1/2 infection. The proposed technology employs a system for detection of IgG1 antibodies in a single competitive immunofluorescence platform by flow cytometry using fluorescently labeled MT-2/MoT cell line mix coupled to a highly sensitive development system (Biotin/Streptavidin/Phycoerythrin). The stability of fluorescent labeling and the antigenicity of MT-2 and MoT cell lines were confirmed upon storage at −20°C for 2, 6, and 12 months. The anti-HTLV-1/2 IgG1 reactivity, expressed as percentage of positive fluorescent cells (PPFC), was evaluated for each target antigen along the titration curve of test serum samples (1:32 to 1:4,096). Upon selection of target cell line and serum dilutions with higher segregation score between groups, the performance of “FIX” and “FIX & PERM” protocols was evaluated. The “FIX” protocol presented excellent performance indices (Se = 92%/Sp = 94%/AUC = 0.96; Se = 96%/Sp = 100%/AUC = 0.99) for the universal (HTLV-1/2 vs. NI) and differential (HTLV-1 vs. HTLV-2) diagnosis of HTLV-1 infection, respectively. Optimization of the “FIX” protocol using the principle of synchronous and asynchronous pairwise analysis further improved the performance of “FC-Duplex IgG1 (HTLV-1/2)”, using the “FIX” protocol for differential diagnosis of HTLV-1 and HTLV-2 infections (Se = 100%/Sp = 100%/AUC = 1.00). In conclusion, the “FC-Duplex IgG1 (HTLV-1/2)” method represents an innovation in the biotechnology segment with the potential to compose a serological kit for differential diagnosis of HTLV-1/2 infection for reference laboratories and blood centers.